Researching user experience with artificial intelligence application for customer care services on e-commerce platform - Giang, Nguyen Thi Phuong; Hung, Do Manh; Huong, Ton Thi; Quyen , Huynh Thi; Thom , Nguyen Thi; Tran , Tran Bao; Tan, Thai Dong (Jurnal Ekonomi Perusahaan, 2024)
This study is conducted in the context of the booming development of e-commerce shopping in Vietnam. The rising demand for online shopping has resulted in increased pressure on workforce optimization and automation of customer service processes on e-commerce platforms. To meet the need for online customer care and response, significant resources in manpower, time, and cost are required. Therefore, to optimize costs, reduce response time, and enhance customer care, applying artificial intelligence to customer service has become a top choice. The purpose of this study is to explore the factors that directly affect the customer service experience using artificial intelligence on e-commerce platforms in Vietnam. This aims to help businesses understand customer feedback and psychology to develop strategies to improve and advance this artificial intelligence application model. This study provides an overview of the factors directly influencing the customer experience in AI-driven customer service on e-commerce platforms. Based on this, it offers managerial implications to enhance the quality of customer service for online businesses operating on e-commerce platforms in Vietnam.